2017
DOI: 10.1007/s11064-017-2201-4
|View full text |Cite
|
Sign up to set email alerts
|

Mdivi-1 Alleviates Early Brain Injury After Experimental Subarachnoid Hemorrhage in Rats, Possibly via Inhibition of Drp1-Activated Mitochondrial Fission and Oxidative Stress

Abstract: Mdivi-1 is a selective inhibitor of mitochondrial fission protein, Drp1, and can penetrate the blood-brain barrier. Previous studies have shown that Mdivi-1 improves neurological outcomes after ischemia, seizures and trauma but it remains unclear whether Mdivi-1 can attenuate early brain injury after subarachnoid hemorrhage (SAH). We thus investigated the therapeutic effect of Mdivi-1 on early brain injury following SAH. Rats were randomly divided into four groups: sham; SAH; SAH + vehicle; and SAH + Mdivi-1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…The expression of c-Myc can restore the mitochondrial volume and induce increased fusion (Graves et al, 2012). Excessive mitochondrial fission has been shown to be involved in the EBI stage following SAH (Wu et al, 2017). In the present study, silencing b-catenin abrogated the protective effect of Pro against the mitochondrial fission phenotype induced by OxyHb.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The expression of c-Myc can restore the mitochondrial volume and induce increased fusion (Graves et al, 2012). Excessive mitochondrial fission has been shown to be involved in the EBI stage following SAH (Wu et al, 2017). In the present study, silencing b-catenin abrogated the protective effect of Pro against the mitochondrial fission phenotype induced by OxyHb.…”
Section: Discussionsupporting
confidence: 54%
“…c-Myc, a down-stream protein of Wnt/b-catenin signaling, contributes to the fusion of mitochondria (Graves et al, 2012). Previous studies have shown that excessive mitochondrial fission is involved in the EBI stage following SAH (Wu et al, 2017). This study, therefore, aims to investigate the protective role of propoxyphene against OxyHb-induced cell apoptosis in primary cortical neurons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of excessive ROS generation in oxidative stress and cardiovascular diseases is commonly accepted [ 30 ], and an appropriate balance between ROS and antioxidants is essential for vasoconstriction [ 31 ]. The effects of Mdivi-1 on oxidative stress are still controversial, although the antioxidative effects of Mdivi-1 are emphasized by most studies [ 28 , 32 ]. A slight increase of ROS level was observed in Mdivi-1-treated WT and Drp1 knockout mouse embryonic fibroblasts (MEFs) in the study by Bordt EA et al [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a very recent study suggested that mdivi‐1 is a poor inhibitor of Drp1 and rather acts as a reversible mitochondrial complex I inhibitor and regulator of ROS production . Regardless, a number of studies have shown that mdivi‐1 improves outcome after OGD and abrogates brain injury after MCAO , subarachnoid haemorrhage , transient global ischaemia and traumatic brain injury .…”
Section: Mitotherapeutics – a New Avenue For Treating Neonatal Brain mentioning
confidence: 99%